Analisis Kepuasan dan Ketidakpuasan Kerja Guru SMA Negeri Kota Madiun - Budi Wibowo, Satrijo (Jurnal Pendidikan, 2010)
Teachersâ work satisfaction becomes one of dimensions for measuring the teachersâ performance in carrying out their educational tasks. Work satisfaction is originated from the establishment of motivation as the unity of concept of needs, encouraging objectives and rewards. Satisfaction is a perception of an individual under which he feels that he has perceived what he hopes through his job, where there is no significant difference between his want and his gain. Work satisfaction is experienced by teachers in relation to their duties and responsibilities as educational staff at schools.This research is intended to identify the determining exogenous variables consisting of schoolsâ organizational climate, head mastersâ leadership, teachersâ professionalism and work motivation, and the manifest variablesâ indicators which directly or indirectly influence the teachersâ work satisfaction at SMUs in Madiun.This research is served under corelational design by confirmatory model which is initiated by a thorough theoretical review. The confirmatory factors is served to measure the model fitness towards the data drawn for analysis. Model fitness implemented in this research is Goodness of Fit (GOF).The analysis is carried out based on the linear relationship among variables under Structural Equation Model (SEM) by Linear Structural Relationship (LISREL).The overall analysis results in conclusions that: determining factor which influence the teachersâ work satisfaction is schoolsâ organizational climate by 0.335, successively the determining factor of headmastersâ leadership and work motivation show the equal score of 0.349Â  and determining factor of teachersâ professionalism shows the least score of 0.282. This recommends a serious attention of the local authority to encourage the development of teachersâ professionalism indicators which can not be inevitably overlooked for educational quality.The total direct influence of motivation towards the teachersâ work satisfaction is 0.349. The confirmatory analysis shows that the teachersâ motivation is fit which is proved by the significance of motivation variable at the level of Î±/2 (0.025) equals to Â± 1.96. Being seen under probability (P) score, all of the motivation dimension variables are less than 0.05 so as to confirm that the loading factor is significant.The overall analysis results in conclusions that: determining factor which influence the teachersâ work satisfaction is schoolsâÂ  dimention recognition with estimate value 0,628. Its means recognition dimention of variable (Y2)Â  to be explanation for 62,8%, and more thanÂ  60,6% influence reserachs for other variable.